IMPLEMENTATION OF PRIMARY SCHOOL MARKETING AND ENTREPRENEURSHIP MANAGEMENT - Sunaengsih, Cucun; Tamam, Badrud; Thahir, Muthahharah; Safitri, Bunga (EARR (Educational Administration Research and Review), 2018)
This study focuses on the implementation of primary school marketing and entrepreneurship, which is facing many challenges in this global age.  Marketing and entrepreneurship are educational quality improvement strategies, which are the most important element of the quality and the advancement of education in an education institution.  The present study employed qualitative approach with survey methods, using observation and in-depth interview to gather accurate data.  The study was conducted in a primary school in West Java, Indonesia.  It was found that (1) the school had adequate facilities to support learning process, (2) the school employed words-of-mouth as marketing strategy, (3) the school used marketing strategy in cooperation with regional coordinator, (4) the school performed routine evaluation with school committee, (5) the school had no entrepreneurship program like that in other private schools, but it implemented entrepreneurship through the students.  Based on these findings, it was concluded that marketing and entrepreneurship needed separate strategies to yield optimum result.Addley, A. (2014). Implementing Professional Learning Communities in a High-Performing School District to Address Stagnating Student Performance.Aditia Pradito. (2016). Strategi Pemasaran Pendidikan dalam Meningkatkan Citra Lembaga Pendidikan Islam. (Tesis). Sekolah Pascasarjana, Universitas Islam Negeri Maulana Malik Ibrahim, Malang.Bridges, C. M., Wilhelm, W. B., Bridges, C. M., Wilhelm, W. B. (2014). Going Beyond Green : The “ Why and How ” of Integrating Sustainability Into the Marketing Curriculum. Journal of Marketing Education, 30(January 2008), 33–46. https://doi.org/10.1177/0273475307312196Green, T. (2015). Flipped Classrooms : An Agenda for Innovative Marketing Education in the Digital Era FLIPPED CLASSROOMS : AN AGENDA FOR INNOVATIVE MARKETING. Marketing Education Review, 25(3), 179–191. https://doi.org/10.1080/10528008.2015.1044851Harrigan, P., Hulbert, B. (2011). How Can Marketing Academics Serve Marketing Practice ? The New Marketing DNA as a Model for Marketing Education. Journal of Marketing Education, 33(3), 253–272. https://doi.org/10.1177/0273475311420234Mocior, E., Kruse, M. (2016). Educational values and services of ecosystems and landscapes - An overview. Ecological Indicators, 60, 137–151. https://doi.org/10.1016/j.ecolind.2015.06.031Moleong, Lexy J. (2011). Metodologi Penelitian Kualitatif. Bandung: Remaja Rosdakarya.Pawlowski, J. M., Bick, M. (2012). The global knowledge management framework: Towards a theory for knowledge management in globally distributed settings business information systems. Electronic Journal of Knowledge Management, 10(1), 92–108.Shir, N., Nikolaev, B. N., Wincent, J. (2019). Entrepreneurship and well-being : The role of psychological autonomy , competence , and relatedness ☆. Journal of Business Venturing, 34(5), 105875. https://doi.org/10.1016/j.jbusvent.2018.05.002Singh, R., Khanduja, D. (2010). SERVQUAL and model of service quality gaps: A framework for determining and prioritizing critical factors from faculty perspective in higher education. International Journal of Engineering Science and Technology, 2, 3297–3304.Sutter, C., Bruton, G. D., Chen, J. (2018). Entrepreneurship as a solution to extreme poverty : A review and future research directions. Journal of Business Venturing, (July 2017), 0–1. https://doi.org/10.1016/j.jbusvent.2018.06.003Wiklund, J., Nikolaev, B., Shir, N., Foo, M., Bradley, S. (2019). Entrepreneurship and well-being : Past , present , and future. Journal of Business Venturing, 34(4), 579–588. https://doi.org/10.1016/j.jbusvent.2019.01.002Windschitl, M., Sahl, K. (2002). Tracing Teachers’ Use of Technology in a Laptop Computer School: The Interplay of Teacher Beliefs, Social Dynamics, and Institutional Culture. American Educational Research Journal Spring, 39(1), 165–205. https://doi.org/10.3102/00028312039001165Wymbs, C. (2011). Digital Marketing : The Time for a New “ Academic Major ” Has Arrived. Journal of Marketing Education, 33(1), 93–106. https://doi.org/10.1177/0273475310392